The Essence of Mursyid Teachers in Sufism Spiritual Education in the Framework of Maqāṣid al-Syarī'ah: The Perspectives of Indonesian Scholars - Akmansyah, Muhammad; Nurnazli, Nurnazli; Mujahid, Amin; Khedr, Tamer Saad Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Sufism spiritual education faces challenges in combining traditional values with modern dynamics, especially in the context of multicultural Indonesia. This study aims to analyze the role, competence, and guidance strategies of mursyid teachers within the framework of maqāṣid al-syarī'ah to bridge the gap between the practice of Sufism and the goals of Islamic syarī’ah. This qualitative research uses a thematic analysis of transcripts from Indonesian scholars' lectures on YouTube, which were selected based on their credibility and relevance to the theme. The data were strengthened by triangulation of classical Sufism texts and consultation with experts. The analysis was carried out through thematic coding to identify patterns related to the role, competence, and guidance strategies of mursyid teachers, then contextualized with the framework of maqāṣid al-syarī'ah. The findings show that mursyid teachers play a crucial role in maintaining spiritual integrity (ḥifẓ al-nafs) and doctrinal adherence (ḥifẓ al-dīn). The core competencies include mastery of syarī’ah, taẓkiyah al-nafs skills, and legitimacy through ijāzah. Adaptive guidance strategies, such as a personal approach and dhikr discipline, have proven to be effective in aligning the practice of Sufism with maqāṣid al-syarī'ah. This study affirms the importance of integrating the framework of maqāṣid al-syarī’ah in the training of mursyid teachers to strengthen the pedagogical effectiveness and ethics of guidance. The implications include recommendations for the development of maqāṣid-based curriculum and capacity building for mursyid in the face of multicultural challenges. This research contributes to the revitalization of Sufism education that is relevant to the needs of the modern era.